Aplikasi Model ARIMA dalam Peramalan Produk Domestik Regional Bruto (PDRB) Pertambangan dan Penggalian Kalimantan Selatan - Hayati, Lia Aulia; Agustina, Neli (Seminar Nasional Official Statistics, 2024)
The Gross Regional Domestic Product (GRDP) of the mining and quarrying sector is one of the leading sectors in South Kalimantan. However, the limitations in mining and quarrying resources pose a threat to the economy of South Kalimantan. Forecasting is conducted to assess the prospects of the mining and quarrying sector, especially since the government's National Medium-Term Development Plan for 2020-2024 targets an economic growth rate for the mining sector of 1.9 - 2.0 percent. This study aims to forecast the GRDP of the mining and quarrying sector in South Kalimantan using the ARIMA model. The research results indicate that the best model is ARIMA (2,1,4) with a Mean Absolute Percentage Error (MAPE) accuracy level of 5.054 percent. The GRDP of the mining and quarrying sector is projected to continue increasing in 2024. The findings of this study are expected to provide information for stakeholders to formulate relevant policies to sustain and enhance the mining sector, particularly in South Kalimantan, given its significant employment generation capacity.